2022
DOI: 10.3390/land11040581
|View full text |Cite
|
Sign up to set email alerts
|

How Does Maize-Cowpea Intercropping Maximize Land Use and Economic Return? A Field Trial in Bangladesh

Abstract: Cultivating multiple crops together can provide numerous benefits, including improved soil health and crop yield. The objective of our study was to determine the optimum planting techniques in intercropping systems, and to maximize their benefits by mitigating competition for resources such as land, space, light interception, and nutrition. The performance of successively planted maize (Zea mays L.) grown with cowpea (Vigna unguiculata L.) was evaluated with a field trial in Bangladesh. The treatments in our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Although legumes generally have taprooted systems along with N-fixing nodules that provide access to atmospheric N [12,13], under the agroecological conditions of this study, the characteristics of maize seem to confer a competitive advantage over cowpea when grown in intercropping. Other studies have also reported a reduction in the productive performance of cowpea when intercropped with maize, compared to sole cropping [24,36]. This may probably occur because cowpea plants, being shorter, are shaded by the maize and have less access to light.…”
Section: Dry Matter Yield and Competition Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although legumes generally have taprooted systems along with N-fixing nodules that provide access to atmospheric N [12,13], under the agroecological conditions of this study, the characteristics of maize seem to confer a competitive advantage over cowpea when grown in intercropping. Other studies have also reported a reduction in the productive performance of cowpea when intercropped with maize, compared to sole cropping [24,36]. This may probably occur because cowpea plants, being shorter, are shaded by the maize and have less access to light.…”
Section: Dry Matter Yield and Competition Indicesmentioning
confidence: 99%
“…Growing two plant species in the same space at the same time leads to competition for resources, particularly for light, water, and minerals [20,21,24]. Maize is a tropical grass with C4 metabolism, and its tall growth provides excellent exposure to solar radiation, which can result in high photosynthesis rates [37,38].…”
Section: Dry Matter Yield and Competition Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, other researchers came with the same result and found that intercropping maize with other crops caused a reduction in each of no. of cobs/plant (Ijoyah et al,2015), no .of grains/ear (Dusa and Roman, 2010;Abd El-Zaher andIsmail, 2014 andSuhi et al, 2022), 100-grain weight (El-Ghobashy et al, 2018), ear weight (Abou El-Enin et al, 2023) and grain yield/plant (Mahdy, 2018 b) compared to maize sole cropping. Moreover, it can be observed generally that intercropping sudan grass with maize produced the highest reduction in grain maize yield and its attributes compared to the other tested forage crops.…”
Section: -1 Grain Yield and Its Attributesmentioning
confidence: 99%
“…A landscape generator typically considers different agricultural land use systems including natural, semi-natural habitats, cropland, and landscape elements. Maize-cowpea intercropping with a temporal niche difference is a better option for sustainable crop production and maximizing land use [94]. Meixiu et al [95] showed that intercropping could be used to obtain more yield on less land with less water by developing and application of dynamic process-based modeling taking into account the acquisition of light and water by the component species.…”
Section: For Improving Land Use and Managementmentioning
confidence: 99%